INFLUENCE OF THE RATE OF SEED DRAPING WITH BENTONITE CLAY AND IRRIGATION REGIME ON THE FORMATION OF THE ROOT SYSTEM OF WINTER WHEAT - Ёдгоров Нормўмин Ғуломович (Web of Journals Publishing, 2025)
In this article, under the conditions of light gray soil of the Kashkadarya region, as a result of the influence of the method of covering the seeds of winter wheat varieties with bentonite clay and irrigation methods on the rood mass, in the Shukron variety up to 32,9-54,2 g and in the Turon variety up to 40,2-68 g.
Keywords: Bentonite clay, winter wheat, irrigatsion rate, seed cover, soil, rood mass,meniral fertilizer, moisture.